A study on the environmental impact on the misused building (bird house) / Raja Nurul Emileen R Zainal - R Zainal, Raja Nurul Emileen (2007)
This dissertation is a study about the environmental impact of the misused building or bird house. It's about the issues about the shop houses that been converted into bird house that bring harm to the people living around the area; the bird's voice that bring noise, the guano smells and other item that related to local authority regulations that entrepreneur tends to break the rules. The area of study is in coastal area that is well-known with bird house. This study is to identify where is the common location that entrepreneur choose to build the bird house. Besides that, this study also is to identify what are the environmental problems that need to be improved and find the effective solutions of the problems. This study also is hoped to gain more information about this issues as this is quite a new industry (bird house-swiftlets) to our country.